Functional compensation precedes recovery of tissue mass following acute liver injury - Chad M. Walesky (Nature Portfolio, 2020)
The liver possesses the ability to regenerate following sudden injury. Here, the authors use single-cell RNA-sequencing and in situ transcriptional analyses to identify a new phase of liver regeneration in mice aimed at maintaining essential functions throughout the regenerative process.